Lithium Nitrate Regulated Sulfone Electrolytes for Lithium Metal Batteries. (28th September 2020) - Fu, Jiale; Ji, Xiao; Chen, Ji; Chen, Long; Fan, Xiulin; Mu, Daobin; Wang, Chunsheng
Abstract: The electrolytes in lithium metal batteries have to be compatible with both lithium metal anodes and high voltage cathodes, and can be regulated by manipulating the solvation structure. Herein, to enhance the electrolyte stability, lithium nitrate (LiNO3 ) and 1, 1, 2, 2‐tetrafuoroethyl‐2′, 2′, 2′‐trifuoroethyl(HFE) are introduced into the high‐concentration sulfolane electrolyte to suppress Li dendrite growth and achieve a high Coulombic efficiency of >99 % for both the Li anode and LiNi0.8 Mn0.1 Co0.1 O2 (NMC811) cathodes. Molecular dynamics simulations show that NO3 − participates in the solvation sheath of lithium ions enabling more bis(trifluoromethanesulfonyl)imide anion (TFSI − ) to coordinate with Li + ions. Therefore, a robust LiN x O y −LiF‐rich solid electrolyte interface (SEI) is formed on the Li surface, suppressing Li dendrite growth. The LiNO3 ‐containing sulfolane electrolyte can also support the highly aggressive LiNi0.8 Mn0.1 Co0.1 O2 (NMC811) cathode, delivering a discharge capacity of 190.4 mAh g −1 at 0.5 C for 200 cycles with a capacity retention rate of 99.5 %. Abstract : A sulfone‐based electrolyte that contains LiNO3 is developed to support two extreme and aggressive electrodes, the lithium metal anode and the LiNi0.8 Mn0.1 Co0.1 O2 (NMC811) cathode, by forming stable electrode electrolyte interfaces with a high Li plating/stripping Coulombic efficiency of 99.0 % and an unprecedentedly high capacity retention of 99.5 % for the NMC811||Li cells. CEI=cathode electrolyte interphase; SEI=solid electrolyte interface; TFSI − =bis(trifluoromethanesulfonyl)imide anion.